The Renin Angiotensin System in Cancer, Lung, Liver and Infectious Diseases - Bhullar, Sukhwinder K.; Tappia, Paramjit S.; Dhalla, Naranjan S. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book of the series on "Advances in Biochemistry in Health and Disease" includes state-of-the-art information on the status of renin-angiotensin system (RAS) in the form of 24 chapters. This book has been organized into three sections: (i) General Implications of RAS in human health and Infectious Diseases, (ii) Lung, Liver and Kidney Diseases, and (iii) Development of Cancer. Each chapter has discussed comprehensive knowledge regarding the molecular and cellular aspects of the role of RAS in the pathophysiology and pharmacotherapy of different disease processes. Biochemical mechanisms associated with angiotensin II type 1 and type II receptors, and angiotensin (1-7) MAS receptors for the occurrence of both harmful and beneficial effects of prolonged activation of RAS in different diseases have been outlined. It is noteworthy to point out that different chapter in this book were prepared by recognized global expertise in the area of inflammation, oxidative stress and signal transduction pathways to highlight the role of RAS in different diseases. It is our sincere hope that this book will be of great interest to both biomedical investigators and health professionals as well as graduate students and postdoctoral fellows all over the world.
1. Implications of renin-angiotensin system in health and disease -- 2. Renin angiotensin system and aging -- 3. The interplay of the renin-angiotensin system and solid organ transplantation -- 4. Correlation between renin angiotensin system and infectious disease -- 5. Emerging contributions of endocrine pathophysiology in virus-related infectious disease -- 6. Understanding the renin-angiotensin system in coronavirus disease 2019 -- 7. Metabolomics approach in differentiating RAS responses in ARDS (Acute respiratory distress syndrome) and SAR-CoV-2 -- 8. A Comprehensive review of the impact of the renin angiotensin system in the liver, lung, infectious diseases and cancers -- 9. Application of biosensors for monitoring changes in renin angiotensin system (RAS) in cancers and lung diseases -- 10. Bioinformatics study on renin angiotensin in lung, and liver cancer using plant-based extracts -- 11. Role of renin-angiotensin system in the pathogenesis and progression of non-alcoholic fatty liver -- 12. The classical and nonclassical renin-angiotensin-aldosterone system in liver cirrhosis -- 13. Renin-angiotensin-aldosterone system role in organ fibrosis -- 14. Role of renin angiotensin-aldosterone system in kidney homeostasis -- 15. Renin-angiotensin system in chronic kidney disease: Implications in stroke outcome -- 16. The renin-angiotensin system and cancer -- 17. Renin-angiotensin system and cancer: From laboratory to clinics -- 18. Role of renin-angiotensin system in cancer cachexia -- 19. Renin angiotensin system activity in different cancers: Mechanistic insight and preclinical studies -- 20. The new dimension of the renin-angiotensin system in the hallmarks of cancer -- 21. Renin-angiotensin system in hematological malignancies -- 22. Renin angiotensin system (RAS): The common thread between cancer and heart failure -- 23. Renin-angiotensin system: a potential therapeutic target for colorectal cancer -- 24. Anticancer role of natural phenolic acids by targeting angiotensin-converting enzyme (ACE) -- 25. Angiotensin-(1-7): A Prospective Cancer Therapeutic.
Keywords: Medicine -- Research; Biology -- Research; Human physiology; Cancer; Cancer -- Treatment; Virology; Therapeutics; Biomedical Research; Human Physiology; Cancer Biology; Cancer Therapy; Virology; Therapeutics